Experimental Study of Fluid Flow Losses at Several Turning Angles - Daud Orba Topayung; Paul M. Rumagit; Toban Tiku Pairunan; Tammy T.V. Pangow; Adolf Tonny Rasuh (Tinta Emas Publisher, 2024)
This research, entitled Experimental Study of Fluid Flow Losses at Turns 30°, 45°, 60° and 90°, is a review of fluid (water) flow in closed channels. Fluid (water) flow in opened and closed channels is influenced by the condition of the container in which the fluid flows. One form of this influence is the occurrence of a condition which is generally known as flow loss. This condition is certainly undesirable because it will cause problems, technically the manifestation is a decrease in pressure including the speed of fluid flow. To find out the real conditions of flow losses, it is necessary to carry out research stages. The research stages were carried out in the form of system design, measurement, testing and data analysis. The system is designed with a pump device, where the fluid is pumped from a holding container, then flows into the installation area or closed channel which is made using ½